2018
DOI: 10.1007/s10393-018-1322-9
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Could Increase the Geographic Extent of Hendra Virus Spillover Risk

Abstract: Disease risk mapping is important for predicting and mitigating impacts of bat-borne viruses, including Hendra virus (Paramyxoviridae:Henipavirus), that can spillover to domestic animals and thence to humans. We produced two models to estimate areas at potential risk of HeV spillover explained by the climatic suitability for its flying fox reservoir hosts, Pteropus alecto and P. conspicillatus. We included additional climatic variables that might affect spillover risk through other biological processes (such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 81 publications
1
26
0
Order By: Relevance
“…31 The risk of a spillover event occurring further south because of the altered range of the flying fox reservoir hosts is hypothesised as being in response to clearing of native food source forests and the effects of climate change. 32,33 Citizens jury processes Adult participants (n = 31), of varied backgrounds, genders and ages, were recruited by an independent professional research service by random-digit-dialling and a social media advertising campaign targeting horse owners. Participants were then selected purposively from the resulting pool to promote sociodemographic diversity within each group, and to make sure that each jury included participants who either owned or worked with horses (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…31 The risk of a spillover event occurring further south because of the altered range of the flying fox reservoir hosts is hypothesised as being in response to clearing of native food source forests and the effects of climate change. 32,33 Citizens jury processes Adult participants (n = 31), of varied backgrounds, genders and ages, were recruited by an independent professional research service by random-digit-dialling and a social media advertising campaign targeting horse owners. Participants were then selected purposively from the resulting pool to promote sociodemographic diversity within each group, and to make sure that each jury included participants who either owned or worked with horses (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Home to a large racing and recreational horse population, Sydney has at least a dozen permanent flying-fox camps located across the metropolitan region [58]. Sydney is yet to be affected by an HeV outbreak but could be at increasing risk of a spillover event as the effects of climate change extend the range of the reservoir hosts further southward [34, 59].…”
Section: Methodsmentioning
confidence: 99%
“…As large areas in north-eastern Australia once covered by eucalypt forests have been cleared for agriculture [32, 33], flying-foxes are encroaching upon human settlements in search of anthropogenic food sources such as fruit trees. The impacts of climate change on flying-fox behaviours and distribution are predicted to markedly expand the geographic range of HeV risk [34]. It is increasingly clear that flying-fox ecology drives the epidemiological dynamics of HeV in bat populations and risk of spillover to horses and, consequently, humans [27, 31].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been found that warmer temperatures prompt bats to leave forests for agricultural areas, where they are more likely to encounter livestock and people and therefore spread disease (Looi and Chua 2007 ). Additionally, climate change may expand the habitat range of bats and thereby increase the range of pathogens they carry (Martin et al 2018 ).…”
Section: The Socioeconomic and Environmental Drivers Of Eidsmentioning
confidence: 99%